Actin filament severing by cofilin dismantles actin patches and produces mother filaments for new patches - Chen, Qian (2013)
BACKGROUND: Yeast cells depend on Arp2/3 complex to assemble actin filaments at sites of endocytosis, but the source of the initial filaments required to activate Arp2/3 complex is not known. RESULTS: We tested the proposal that cofilin severs actin filaments during endocytosis in fission yeast cells using a mutant cofilin defective in severing. We used quantitative fluorescence microscopy to track mGFP-tagged proteins, including early endocytic adaptor proteins, activators of Arp2/3 complex and actin filaments. Consistent with the hypothesis, actin patches disassembled far slower in cells depending on severing-deficient cofilin than wild type cells. Even more interesting, actin patches assembled slowly in these cofilin mutant cells. Adaptor proteins End4p and Pan1p accumulated and persisted at endocytic sites more than 10 times longer than in wild type cells, followed by slow put persistent recruitment of activators of Arp2/3 complex, including WASP and myosin-I. Mutations revealed that actin filament binding sites on adaptor proteins Pan1p and End4p contribute to initiating actin polymerization in actin patches. CONCLUSIONS: We propose a “sever, diffuse and trigger” model for the nucleation of actin filaments at sites of endocytosis whereby cofilin generates actin filament fragments that diffuse through the cytoplasm, bind adapter proteins at nascent sites of endocytosis and serve as mother filaments to initiate the autocatalytic assembly of the branched actin filament network of each new patch. This hypothesis explains the source of the “mother filaments” that are absolutely required for Arp2/3 complex to nucleate polymerization.